I. Meşrutiyet Meclis-i Mebusan'ında parlamento denetiminde öne çıkan mebuslar - GENÇKAYA, ÖMER FARUK (My University, 2021)
Osmanlı Devleti’nin anayasal sisteme geçmesinden kısa bir süre sonra Meclis-i Mebusan açıldı. İlk meclise sınırlı da olsa hükümeti denetlemeye yönelik bazı denetim araçları verilmişti. Büyük bir coğrafyaya sahip olan Osmanlı Devleti’nin dört bir yanından İstanbul’a gelen mebuslar kozmopolit bir meclis yapısı oluşturdu. Farklı etnik kökenlere sahip bu mebuslar Dahili Nizamname’de düzenlenen bir parlamenter denetim aracı olan istizaha (gensoru) sıklıkla başvurdular. Bir parlamento kültürü olmamasına karşın, ortak sorunların göreceli bir “serbest” tartışma ortamında ifade edilmesi, dolaylı olarak padişahın sorgulanmasını da gündeme getirdi. Bu gelişme, öteki nedenlerle birlikte parlamentonun 30 yıl tatil edilmesine yol açtı. Bu çalışmada, İlk Osmanlı Meclis-i Mebusan’ında, parlamenter denetim sürecinde öne çıkan mebusların etkinlikleri incelenecektir.

Shortly after the transition of the Ottoman Empire to the constitutional system, the Parliament was opened. The first parliament was provided some means of control, albeit limited, to control the government. Deputies who came to Istanbul from all over the Ottoman Empire, which had large geography, formed a cosmopolitan assembly structure. These deputies of different ethnic origins frequently resorted to the istizah (interpellation), a parliamentary control tool regulated in the Internal Regulations. Despite the lack of a parliamentary culture, the expression of common problems in a relatively “free” discussion environment indirectly led to questioning of the Sultan, too. This development, along with other reasons, led to the 30-year recess of parliament. In this study, the activities of the prominent deputies in the parliamentary control process in the First Ottoman Parliament will be examined.
Keywords: I. Meşrutiyet; Osmanlı Parlamentosu; Parlamenter Denetim; Meclis-i Mebusan; İstizah; The First Constitutional Monarchy; Ottoman Parliament; Parliamentary Control; Interpellation